Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c8tb01759j
|View full text |Cite
|
Sign up to set email alerts
|

Improved photodynamic effect through encapsulation of two photosensitizers in lipid nanocapsules

Abstract: Encapsulation of two photosensitizers in lipid nanocapsules leads to enhanced photodynamic therapy efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For instance, chlorin E6 was incorporated into nanoparticles via formation of ion complexes in order to increase absorption by the tumor (Lee et al, 2013). Encapsulation of drugs into delivery systems has been as area of extensive research over the last years (Rout et al, 2017;Barras et al, 2018;Fasiku et al, 2021;Karges et al, 2021;Mitchell et al, 2021). Although bioconjugation and encapsulation with targeting moieties seem to be critical approaches in order to develop more effective and specific PSs, it should also be borne in mind that an ideal PS should achieve high quantum yield, display long-wave absorption, cause low dark toxicity, demonstrate favorable pharmacokinetic properties, have high purity and stability (Wöhrle et al, 1998).…”
Section: History Of Photodynamic Therapymentioning
confidence: 99%
“…For instance, chlorin E6 was incorporated into nanoparticles via formation of ion complexes in order to increase absorption by the tumor (Lee et al, 2013). Encapsulation of drugs into delivery systems has been as area of extensive research over the last years (Rout et al, 2017;Barras et al, 2018;Fasiku et al, 2021;Karges et al, 2021;Mitchell et al, 2021). Although bioconjugation and encapsulation with targeting moieties seem to be critical approaches in order to develop more effective and specific PSs, it should also be borne in mind that an ideal PS should achieve high quantum yield, display long-wave absorption, cause low dark toxicity, demonstrate favorable pharmacokinetic properties, have high purity and stability (Wöhrle et al, 1998).…”
Section: History Of Photodynamic Therapymentioning
confidence: 99%
“…Barras et al . (74) reported that the use of combination of two PS (Protoporphyrin IX, (PpIX) and Hypericin, (Hy)) encapsulated inside liposomes (LNCs) favored PDT. The spectroscopic studies showed that the encapsulation of both PS in the lipid core increases their solubilization and photophysical properties; besides, the encapsulation of both Ps into a liposome (PpIX–Hy‐loaded LNC25) incremented the phototoxicity in HeLa and MDA‐MB‐232 cells line and provided a synergistic effect.…”
Section: Use Of Drug Delivery Systems For Photosensitizersmentioning
confidence: 99%
“…The monomeric form of hypericin has been previously reported into lipid membrane structures 270 and nanoparticles. 265 The absorption spectrum of monomeric HYP has also been observed for hypericin in other systems such as biodegradable PLA NPs, 261 anti-HSA monoclonal antibodies, 253 solid lipid nanoparticles 259 or lipid nanocapsules. 258,265 In this latter example, a 3 nm hypsochromic shift regarding DMSO λmax, as in HYP@1, was described.…”
Section: Hypericin Encapsulationmentioning
confidence: 94%
“…265 The absorption spectrum of monomeric HYP has also been observed for hypericin in other systems such as biodegradable PLA NPs, 261 anti-HSA monoclonal antibodies, 253 solid lipid nanoparticles 259 or lipid nanocapsules. 258,265 In this latter example, a 3 nm hypsochromic shift regarding DMSO λmax, as in HYP@1, was described. 258 A value of 0.01-0.23% w/w was calculated as drug loading in HYP@1, which is quite similar to some examples of hypericin-loaded systems in Table 4.7.…”
Section: Hypericin Encapsulationmentioning
confidence: 94%
See 1 more Smart Citation